2015
DOI: 10.1002/mabi.201500069
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Microcarriers of Poly(Lactide-co-Glycolide) and Nano-Hydroxyapatite Decorated with IGF-1 via Polydopamine Coating for Enhancing Cell Proliferation and Osteogenic Differentiation

Abstract: In this study, insulin-like growth factor 1 (IGF-1) was successfully immobilized on the poly(lactide-co-glycolide)/hydroxyapatite (PLGA/HA) and pure PLGA microcarriers via polydopamine (pDA). The results demonstrated that the pDA layer facilitated simple and highly efficient immobilization of peptides on the microcarriers within 20 min. Mouse adipose-derived stem cells (ADSCs) attachment and proliferation on IGF-1-immobilized microcarriers were much higher than non-immobilized ones. More importantly, the IGF-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 38 publications
(53 reference statements)
2
46
0
Order By: Relevance
“…Similarly, the specific outgrowth rate and mean cell diameter have been maintained post-harvest, demonstrating that the microcarrier process has not affected these BM-hMSC characteristics. In contrast, the osteogenic potential of the BM-hMSCs decreased for all conditions (P < 0.01), which should be further investigated if the BM-hMSCs are to be used for clinical indications relating to the production of collagen.There is the potential however, for this type of clinical indication, that biodegradable microcarriers could be directly implanted as a cellscaffold construct to support the regeneration of bone tissue [33], removing the need for cell harvest altogether. This comparison of performance demonstrates that HPL is a viable alternative to FBS for the microcarrier culture of BM-hMSCs and has the potential to be taken forward to support further process development and scale-up.The increased consistency in growth between donors in HPL will also benefit the development of both patient specific and off-the-shelf BM-hMSC therapies, allowing for increased production rates and shorter processing times.…”
Section: Microcarrier Expansion Of Bm-hmscsmentioning
confidence: 99%
“…Similarly, the specific outgrowth rate and mean cell diameter have been maintained post-harvest, demonstrating that the microcarrier process has not affected these BM-hMSC characteristics. In contrast, the osteogenic potential of the BM-hMSCs decreased for all conditions (P < 0.01), which should be further investigated if the BM-hMSCs are to be used for clinical indications relating to the production of collagen.There is the potential however, for this type of clinical indication, that biodegradable microcarriers could be directly implanted as a cellscaffold construct to support the regeneration of bone tissue [33], removing the need for cell harvest altogether. This comparison of performance demonstrates that HPL is a viable alternative to FBS for the microcarrier culture of BM-hMSCs and has the potential to be taken forward to support further process development and scale-up.The increased consistency in growth between donors in HPL will also benefit the development of both patient specific and off-the-shelf BM-hMSC therapies, allowing for increased production rates and shorter processing times.…”
Section: Microcarrier Expansion Of Bm-hmscsmentioning
confidence: 99%
“…The hMSCs seeded on nanocomposite PCL/HA scaffolds in 12-well plate and showed high proliferation in HA concentration-dependent manner as compared to Neat-PCL (Figure 4). Additionally, previous studies have demonstrated that PCL/HA-based scaffolds showed high proliferation and osteogenic differentiation in human dental pulp stem cells (hDPSCs) and mouse adipose-derived stem cells (ADSCs) (33, 34). Interestingly, magnetic bioinspired hybrid nanocomposite collagen-hydroxyapatite scaffolds enhanced cellular proliferation and restored bone generation (35, 36).…”
Section: Resultsmentioning
confidence: 99%
“…Specific proteins and peptides that promote bone regrowth and healing have also been attached to implant materials through polydopamine coatings, resulting in strong immobilization and improved bone regeneration . This includes the attachment of growth factors to promote the attachment and osteogenic differentiation of adipose‐derived stem cells, enhancing healing and inhibiting scarring in rabbits . Also, bone morphogenetic protein and derived peptides have been absorbed onto polydopamine surfaces, leading to increased expression of markers of osteogenesis in human stem cells, and promoting bone formation in mice …”
Section: Applications Of Catecholamine Polymersmentioning
confidence: 99%